Listening to Community to Improve Breastfeeding Friendliness: Findings From a Community Readiness Assessment on Breastfeeding - Frieson, Tomeka; Masterson, Amelia; Tran, Victoria; Douglass, Frankie; Duffany, Kathleen (Health Promotion Practice, 2025)
Breastfeeding is a key nutritional behavior for infants during their first years of life. While prenatal breastfeeding intentions do not differ significantly between non-Hispanic Black and White mothers, the ability to meet those intentions decreases over time, and to a greater extent among Black mothers. This is partially due to environments inadequately supportive of individuals' breastfeeding needs (i.e., not breastfeeding-friendly). The Community Readiness Assessment is a powerful tool to assess a community's readiness to take action on pressing health issues. While it is frequently used to understand readiness to prevent negative health outcomes, this study explores how it can be used to understand readiness to promote breastfeeding friendliness and subsequently identify appropriate intervention strategies. Between November 2020 and June 2021, we conducted interviews with 23 key respondents in New Haven, Connecticut, representing five community sectors. Respondents scored five dimensions of readiness on a 9-point scale (1 = no awareness, 9 = community ownership). The overall community readiness score was 4.2, denoting the "preplanning" stage of readiness. The highest-scoring readiness dimension was "community knowledge about the issue" (mean score: 4.5), and the lowest-scoring dimension was "resources related to the issue" (mean score: 3.3). Small business owners reported the highest readiness score by sector (mean score: 5.0), while large employers reported the lowest (mean score: 3.1). Scores stratified by both sector and dimension revealed specific areas within the community where readiness-level-appropriate interventions could be implemented. This study highlights the benefit of assessing community readiness prior to intervention to identify tailored, equitable, and effective intervention strategies.
Keywords: Active listening; Breast feeding; Breastfeeding; Breastfeeding promotion; Community Readiness Assessment; Community health; Intervention (counseling); Psychological intervention; Scale (ratio); breastfeeding; breastfeeding-friendly; community; community assessment; community readiness; dept.hhs; public health practice

The Business Case for Breastfeeding: Identifying Which Barriers and Facilitators Employers Prioritize When Supporting Breastfeeding Employees in the Workplace - Frieson, Tomeka; Muhammad, Tila; Belyea, Monica; Cole, Ayeisha; Ray, Natasha; Duffany, Kathleen (Journal of Human Lactation, 2026)
Keywords: Breast feeding; Breastfeeding; Phone; Private sector; Public health; Space (punctuation); breastfeeding; breastfeeding barriers; breastfeeding benefits; breastfeeding experience; breastfeeding knowledge; breastfeeding promotion; breastfeeding support; dept.hhs; maternal health; public health; qualitative methods; social support

The Effects of Length of Residence and Exposure to Violence on Perceptions of Neighborhood Safety in an Urban Sample. - Guo, Monica; O'Connor Duffany, Kathleen; Shebl, Fatma M; Santilli, Alycia; Keene, Danya E (Journal of Urban Health, 2018)
Perceptions of neighborhood safety shape the well-being of individuals and communities, affecting neighborhood walkability, associated physical activity behaviors, and health conditions. However, less is known about the factors that determine perceptions of safety. One factor that may affect perceptions of neighborhood safety is the length of time someone has lived in their neighborhood. We use a representative, adult sample of urban low-income residents from the 2015 New Haven Health Survey (n = 1189) to investigate the associations between length of residence (new residents of < 1 year in neighborhood versus longer-term residents of 1 or more years in neighborhood) and perceptions of neighborhood safety (whether feeling unsafe to walk at night). We then examine the potential moderating effect of exposure to neighborhood violence on these associations. We find that the association between length of residence and perceived safety differs by exposure to neighborhood violence. Among those unexposed to neighborhood violence, longer-term neighborhood residents were more likely to feel unsafe compared to new residents (OR = 2.03, 95% CI 1.19, 3.45). Additionally, the effect of exposure to violence on feelings of safety was larger for new residents (OR = 9.10, 95% CI 2.72, 30.44) compared to longer-term residents (OR = 1.88, 95% CI 1.28, 2.77). Our findings suggest that length of residence may have implications for feelings of safety, and that experiences of violence may uniquely contribute to feelings of unsafety among new residents. These findings hold implications for interventions and policy efforts aimed at neighborhood safety improvements through community development, housing, or city urban planning initiatives, particularly for new neighborhood residents or those who experience neighborhood violence.
Keywords: *Exposure to Violence/px [Psychology]; *Exposure to Violence/sn [Statistics & Numerical Data]; *Poverty/px [Psychology]; *Poverty/sn [Statistics & Numerical Data]; *Residence Characteristics/sn [Statistics & Numerical Data]; *Safety/sn [Statistics & Numerical Data]; *Urban Population/sn [Statistics & Numerical Data]; Adult; Age Factors; Aged; Exposure to Violence; Exposure to violence; Female; Humans; Length of residence; Male; Middle Aged; Neighborhood; Perceptions of safety; Poverty; Residence Characteristics; Residential stability; Safety; Urban Population; Violence; Young Adult; adult; age; aged; demography; dept.pch; exposure to violence; female; human; male; middle aged; peer-reviewed; poverty; psychology; safety; urban population; young adult

Availability, accessibility, utilization: n-depth interviews with food insecure residents and emergency food providers in new haven, CT - Carroll, Grace; Keene, Danya; Santilli, Alycia; Johannes, Joy; Ickovics, Jeannette; Duffany, Kathleen O’Connor (Journal of Hunger & Environmental Nutrition, 2019)
Approximately 34% of residents from New Haven’s six lowest-income neighborhoods are food insecure, significantly higher than the rest of Connecticut and country (both approximately 12%). To understand the availability, accessibility, and utility of emergency food programs, we conducted 34 semi-structured qualitative interviews with 20 food insecure residents and 14 emergency food providers. Many depend on food programs as a long-term strategy of supplementing groceries rather than a temporary solution in emergency situations; providers are struggling to meet this demand. Transportation and time are barriers to accessing food from programs. Policies and food programs should focus on disseminating accurate information, streamlining policies and practices, and supporting and expanding food programs to meet population need.
Keywords: Food insecurity; adult; article; community health; community-based participatory research; dept.pch; emergency; emergency food programs; food insecurity; food pantries; human; interview; participatory research; peer-reviewed; public health; resident; soup kitchen; soup kitchens

Black fathers' views on breastfeeding facilitators, barriers, and support services: Insights from a qualitative community-based participatory research study - Rios, Jasmine; Frieson, Tomeka; Ray, Natasha; Edwards, Doug; Pérez-Escamilla, Rafael; O'Connor Duffany, Kathleen (Maternal & Child Nutrition, 2024)
Despite the persistence of breastfeeding racial and ethnic disparities in the United States, little is known about Black fathers' perceptions of breastfeeding and breastfeeding support services (e.g., maternity hospital-based care and lactation management care). This qualitative, community-based participatory research study reports Black fathers' perceptions of barriers and facilitators to breastfeeding, including the provision of breastfeeding support services in Connecticut. A focus group guide was co-developed with community partners and adapted from the Barrier Analysis Tool to identify breastfeeding facilitators, barriers, and service improvement areas. Four focus groups were conducted with 30 Black fathers who were Connecticut residents with a child under 3 years old. Qualitative data were analyzed using rapid template analysis involving deductive and inductive coding. We identified factors influencing breastfeeding and fathers' ability to support breastfeeding across all levels of the Socio-Ecological Model. Facilitators included high paternal breastfeeding knowledge, paternal breastfeeding involvement, parents' shared decision-making, extensive maternity hospital discharge support, ongoing breastfeeding support into the postnatal period, availability of community breastfeeding resources, and designated spaces for public breastfeeding. Barriers included low paternal breastfeeding knowledge, familial discouragement, insufficient prenatal breastfeeding education, exclusion of the father from breastfeeding support services, and stigma against breastfeeding in public. Understanding breastfeeding perceptions among members of a mother's support network, including their partners, is key for developing effective person- and family-centered breastfeeding education and counseling services that are well coordinated from the prenatal to postnatal periods with strong direct engagement from fathers.
Keywords: dept.pch; peer-reviewed

Barriers and facilitators to exclusive breastfeeding among Black mothers: A qualitative study utilizing a modified Barrier Analysis approach - Tran, Victoria; Reese Masterson, Amelia; Frieson, Tomeka; Douglass, Frankie; Pérez-Escamilla, Rafael; O'Connor Duffany, Kathleen (Maternal & Child Nutrition, 2022)
Breastfeeding has health benefits for both infants and mothers, yet Black mothers and infants are less likely to receive these benefits. Despite research showing no difference in breastfeeding intentions by race or ethnicity, inequities in breastfeeding rates persist, suggesting that Black mothers face unique barriers to meeting their breastfeeding intentions. The aim of this study is to identify barriers and facilitators that Black women perceive as important determinants of exclusively breastfeeding their children for at least 3 months after birth. Utilizing a Barrier Analysis approach, we conducted six focus group discussions, hearing from Black mothers who exclusively breastfed for 3 months and those who did not. Transcripts were coded starting with a priori parent codes based on theory-derived determinants mapped onto the Socioecological Model; themes were analysed for differences between groups. Facilitators found to be important specifically for women who exclusively breastfed for 3 months include self-efficacy, lactation support, appropriate lactation supplies, support of mothers and partners, prior knowledge of breastfeeding, strong intention before birth and perceptions of breastfeeding as money-saving. Barriers that arose more often among those who did not exclusively breastfeed for 3 months include inaccessible lactation support and supplies, difficulties with pumping, latching issues and perceptions of breastfeeding as time-consuming. Lack of access to and knowledge of breastfeeding laws and policies, as well as negative cultural norms or stigma, were important barriers across groups. This study supports the use of the Socioecological Model to design multicomponent interventions to increase exclusive breastfeeding outcomes for Black women.
Keywords: barrier analysis; breastfeeding; dept.csc; dept.pch; focus group; peer-reviewed; public health; qualitative methods; social factors; sociocultural analyses

Bridging the response to mass shootings and urban violence: exposure to violence in New Haven, Connecticut - Santilli, Alycia; Duffany, Kathleen O'Connor; Carroll-Scott, Amy; Thomas, Jordan; Greene, Ann; Arora, Anita; Agnoli, Alicia; Gan, Geliang; Ickovics, Jeannette (American Journal of Public Health, 2017)
We have described self-reported exposure to gun violence in an urban community of color to inform the movement toward a public health approach to gun violence prevention. The Community Alliance for Research and Engagement at Yale School of Public Health conducted community health needs assessments to document chronic disease prevalence and risk, including exposure to gun violence. We conducted surveys with residents in six low-income neighborhoods in New Haven, Connecticut, using a neighborhood-stratified, population-based sample (n=1189; weighted sample to represent the neighborhoods, n = 29 675). Exposure to violence is pervasive in these neighborhoods: 73% heard gunshots; many had family members or close friends hurt (29%)or killed (18%)by violent acts. Although all respondents live in low-income neighborhoods, exposure to violence differs by race/ ethnicity and social class. Residents of color experienced significantly more violence than did White residents, with a particularly disparate increase among young Black men aged 18 to 34 years. While not ignoring societal costs of horrific mass shootings, we must be clear that a public health approach to gun violence prevention means focusingonthedualepidemicofmass shootings and urban violence.
Keywords: Adolescent; Adult; African American; African Americans; Aged; Caucasian; Connecticut; European Continental Ancestry Group; Exposure to Violence; Female; Humans; Male; Mass Casualty Incidents; Middle Aged; Poverty Areas; Prevalence; Risk Factors; Self Report; Surveys and Questionnaires; Urban Population; Wounds, Gunshot; adolescent; adult; aged; dept.pch; ethnology; exposure to violence; female; gunshot injury; human; male; mass disaster; middle aged; poverty; prevalence; questionnaire; risk factor; self report; statistics and numerical data; urban population

Building Power for Health: CARE’s Community Health Leaders Program - Santilli, Alycia; Morales, Sofia I.; Hodgson, Nora; Williams, Janice M.; Alvarez-Diaz, Isabel; Cole, Ayeisha; Abrams, Jasmine; Breny, Jean M.; O’Connor Duffany, Kathleen (Health Promotion Practice, 2026)
Individuals who face the daily impact of health inequities and their social drivers have knowledge and invaluable insights about solutions that are feasible at the local level. Community organizing is a dynamic and proven approach for building power among residents to identify community priorities, advocate for change, and co-create solutions to community issues, which has been applied to advance community priorities in the public health field. To build on evidence and further cultivate a pathway to strengthen community power and capacity within a public health framework, the Community Alliance for Research and Engagement (CARE), a health equity-focused partnership among Southern Connecticut State University, Yale School of Public Health, and the New Haven community, developed and implemented a new initiative, the Community Health Leaders (CHL) Program. The CHL program provides a model for community-centered leadership development as a strategy for advancing health equity. By equipping residents with the skills and support needed to advocate for change, CHL contributes to strengthening community power. Ultimately, continued investment in programs like CHL has the potential to create responsive public health programs and policies, reduce health inequities, and improve health outcomes. © 2026 Society for Public Health Education
Keywords: advocacy; community health; community organizing; dept.hhs; empowerment; health disparities; health equity; health promotion; lay leader advisors; social determinants of health; training

Utilizing the program impact pathways framework for improving COVID-19 vaccine confidence and uptake: demonstrations of multi-sector collaboration from two geographies in Connecticut - Beaulieu, A.; LaMonaca, Katherine; Higginbottom, Jackson; Foster, Jaime; Macklin, Bernard; Muhammad, Tila; Schwartz, Elizabeth; Comerford, Beth; Santilli, Alycia; Duffany, Kathleen; Pérez‐Escamilla, Rafael (Vaccine, 2025)
Keywords: 2019-20 coronavirus outbreak; Biology; Coronavirus disease 2019 (COVID-19); Infectious disease (medical specialty); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); Virology; dept.hhs

The implementation of a nutrition intervention in food pantries: the spirit of SWAP - Morales, Sofia I.; Vicente, Genesis; LaMonaca, Katherine; Rios, Jasmine; Cunningham, Shayna D.; Higginbottom, Jackson; Mathios, Erin; Werlin, Steve; Cramer, James; Santilli, Alycia; O’Connor Duffany, Kathleen (Health Promotion Practice, 2023)
Background. Food insecurity, affecting approximately 10% of the U.S. population, with up to 40% or higher in some communities, is associated with higher rates of chronic conditions and inversely associated with diet quality. Nutrition interventions implemented at food pantries are an effective strategy to increase healthy food choices and improve health outcomes for people experiencing food and nutrition insecurity. Supporting Wellness at Pantries (SWAP), a stoplight nutrition ranking system, can facilitate healthy food procurement and distribution at pantries. Purpose. Guided by the RE-AIM Framework, this study assesses the implementation and outcomes of SWAP as nutritional guidance and institutional policy intervention, to increase procurement and distribution of healthy foods in pantries. Method. Mixed-methods evaluation included observations, process forms, and in-depth interviews. Food inventory assessments were conducted at baseline and 2-year follow-up. Results. Two large pantries in New Haven, Connecticut, collectively reaching more than 12,200 individuals yearly, implemented SWAP in 2019. Implementation was consistent prepandemic at both pantries. Due to COVID-mandated distribution changes, pantries adapted SWAP implementation during the pandemic while still maintaining the ?spirit of SWAP.? One pantry increased the percentage of Green foods offered. Challenges to healthy food distribution are considered. Discussion. This study has implications for policy, systems, and environmental changes. It shows the potential for SWAP adoption at pantries, which can serve as a guide for continued healthy food procurement and advocacy. Maintaining the ?spirit of SWAP? shows promising results for food pantries looking to implement nutrition interventions when standard practice may not be possible.
Keywords: dept.hhs; peer-reviewed

COVID-19 Vaccine Acceptance and Access Among Black and Latinx Communities - Balasuriya, Lilanthi; Santilli, Alycia; Morone, Jennifer; Ainooson, Jessica; Roy, Brita; Njoku, Anuli; Mendiola-Iparraguirre, Andrea; O’Connor Duffany, Kathleen; Macklin, Bernard; Higginbottom, Jackson; Fernández-Ayala, Celina; Vicente, Genesis; et al. (JAMA Network Open, 2021)
Black and Latinx communities have faced disproportionate harm from the COVID-19 pandemic. Increasing COVID-19 vaccine acceptance and access has the potential to mitigate mortality and morbidity from COVID-19 for all communities, including those most impacted by the pandemic.To investigate and understand factors associated with facilitating and obstructing COVID-19 vaccine access and acceptance among Black and Latinx communities.This community-partnered qualitative study conducted semistructured, in-depth focus groups with Black and Latinx participants from March 17 to March 29, 2021, using a secure video conferencing platform. Participants were recruited through emails from local community-based organizations, federally qualified health centers, social service agencies, the New Haven, Connecticut, Health Department, and in-person distribution of study information from community health workers. A total of 8 focus groups were conducted, including 4 in Spanish and 4 in English, with 72 participants from a diverse range of community roles, including teachers, custodial service workers, and health care employees, in New Haven, Connecticut. Data were analyzed from March 17 to July 30, 2021.Interviews were audio-recorded, transcribed, translated, and analyzed using an inductive content analysis approach. Themes and subthemes were identified on the acceptability and accessibility of the COVID-19 vaccine among participants who identified as Black and/or Latinx.Among 72 participants, 36 (50%) identified as Black, 28 (39%) as Latinx, and 8 (11%) as Black and Latinx and 56 (78%) identified as women and 16 (22%) identified as men. Participants described 3 major themes that may represent facilitators and barriers to COVID-19 vaccinations: pervasive mistreatment of Black and Latinx communities and associated distrust; informing trust via trusted messengers and messages, choice, social support, and diversity; and addressing structural barriers to vaccination access.The findings of this qualitative study may impact what health care systems, public health officials, policy makers, health care practitioners, and community leaders can do to facilitate equitable uptake of the COVID-19 vaccine. Community-informed insights are imperative to facilitating COVID-19 vaccine access and acceptance among communities hardest hit by the pandemic. Preventing the further widening of inequities and addressing structural barriers to vaccination access are vital to protecting all communities, especially Black and Latinx individuals who have experienced disproportionate death and loss from COVID-19.
Keywords: Adolescent; Adult; African American; African Americans; Article; Black person; COVID-19 Vaccines; Connecticut; Female; Focus Groups; Health Services Accessibility; Hispanic; Hispanic Americans; Humans; Male; Middle Aged; Patient Acceptance of Health Care; SARS-CoV-2 vaccine; South and Central America; Trust; Young Adult; adolescent; adult; aged; community; content analysis; controlled study; coronavirus disease 2019; dept.pch; e-mail; employment; female; health auxiliary; health behavior; health care access; health care delivery; health care personnel; health care system; health center; health disparity; human; information processing; male; medical information; middle aged; outcome assessment; pandemic; patient attitude; peer-reviewed; public health service; qualitative research; risk factor; semi structured interview; social support; social worker; teacher; trust; vaccination; videoconferencing; young adult

Community-engaged design of a virtual diabetes prevention program intervention with care coordination - LaMonaca, Katherine; Campbell-Britton, Meredith; Duffany, Kathleen O’Connor; Comerford, Beth P.; Morales, Sofia I.; Ayettey, Rockiy G.; Astudillo, Katia; Swansiger, Mary; Kidd, Claudette; Rue, Bailee; Santilli, Alycia; Njike, Valentine Y.; et al. (BMC Health Services Research, 2026)
The Diabetes Prevention Program (DPP) is an evidence-based approach to prevent Type 2 Diabetes (T2D), the leading cause of morbidity and mortality in the United States. Despite demonstrated benefits, acceptability and uptake of DPPs remain low, especially among communities with low incomes at increased risk for diabetes. The Yale-Griffin Prevention Research Center led the design of a community-engaged virtual DPP (vDPP) intervention and assessed its feasibility of implementation in two contrasting settings.
Keywords: Prediabetes; Prevention; Telemedicine; Type 2 Diabetes; dept.hhs